Ofuji disease: a rare dermatosis and its challenging therapeutic approach - Fernanda Freitas de Brito; Antonio Carlos Ceribelli Martelli; Maria Lopes Lamenha Lins Cavalcante; Ana Cecília Versiani Duarte Pinto; Gabriela Itimura; Cleverson Teixeira Soares (Sociedade Brasileira de Dermatologia, 2016)
Abstract: Eosinophilic pustular folliculitis (EPF) or Ofuji disease is a rare dermatosis, prone to recurrence and chronicity. The peak incidence occurs in the third decade of life and its exact etiology remains unknown. Evidence suggests that the expression of adhesion molecules and the production of cytokines activate the follicular unit, but the stimulus that triggers these changes remains unclear. The three clinical variants reported in the literature include classic EPF, immunosuppression-associated EPF, and infancy-associated EPF. We report a case of eosinophilic pustular folliculitis with peculiar epidemiological characteristics, which represents a challenging therapeutic scenario.